Tradisi Kepesantrenan Pondok Pesantren Roudlotul Ta’limil Quran Dalam Perspektif Pemikiran Kritis Herbert Marcuse - Rohman, Ahmad Yani Fathur (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
This article discusses the Islamic boarding school tradition of the Roudlotul Ta'limil Quran (PPRQ) Islamic Boarding School in the perspective of Herbert Marcuse's critical thinking. The uniqueness of this pesantren is that it not only teaches religious and general sciences, but also teaches skills and sosial interactions with the surrounding community. Since the Pandemic, PPRQ has experienced rapid changes in the culture of pesantren, especially the digitalization process. There is a condition called the condition of the abundance of information that causes the emergence of a one-dimensional society as in the book One-Dimensional Man by Herbert Marcuse. However, Marcuse himself has offers to get out of this situation which is popular with Herbert Marcuse's critical thinking. Herbert Marcuse's concept of critical thinking is applied to PPRQ which states that independence and sosial sensitivity are the main weapons for the war against a one-minded society or a one-dimensional society. Herbert Marcuse offers critical education and aesthetic education to awaken people, in this case the PPRQ students. The existence of PPRQ with all its dynamics as an educational institution as well as a sosial institution that puts forward a critical, creative and innovative attitude will be a representative of critical education and aesthetic education itself. The result of PPRQ education is the emergence of students who are able to make people who hold fast to noble cultures to become their identity. This will be a solution to prevent the occurrence of a uniform global society of one thought that characterizes a one-dimensional society.